UNUSUAL VENOUS DRAINAGE OF THE HEAD AND NECK - HUMBERTO FERREIRA ARQUEZ, (International Journal of Pharma and Bio Sciences, 2014)
Variations in drainage veins of the face and neck are important not only for the anatomist but also surgeon. In view of this significance a total of 13 cadavers with different age groups were used for this study. The head and neck region (26 sides) were dissected carefully and photographed in the Morphology Laboratory at the University of Pamplona. Anatomical variation and unusual pattern of drainage was found in a 75-year-old male cadaver with unilateral absence of external jugular vein. The lingual vein and the superior thyroid vein had transverse venous connections which drained into an arch venous located between the primitive carotid artery and the superior thyroid artery. This arch venous draining above in the common facial vein and down into the internal jugular vein. Knowledge of anatomic and morphologic variations in the superficial veins of the head and neck is essential to carry out successful surgical procedures.